Development and In-vitro Characterization of Fish Oil Oleogels Containing Benzoyl Peroxide and Salicylic Acid as Keratolytic Agents - Rehman, K.; Tan, C. M.; Zulfakar, M. H. (Drug Research, 2014)
Topical keratolytic agents such as benzoyl peroxide (BP) and salicylic acid (SA) are one of the common treatments for inflammatory skin diseases. However, the amount of drug delivery through the skin is limited due to the stratum corneum. The purposes of this study were to investigate the ability of fish oil to act as penetration enhancer for topical keratolytic agents and to determine the suitable gelator for formulating stable fish oil oleogels. 2 types of gelling agents, beeswax and sorbitan monostearate (Span 60), were used to formulate oleogels. To investigate the efficacy of fish oil oleogel permeation, commercial hydrogels of benzoyl peroxide (BP) and salicylic acid (SA) were used as control, and comparative analysis was performed using Franz diffusion cell. Stability of oleogels was determined by physical assessments at 20°C and 40°C storage. Benzoyl peroxide (BP) fish oil oleogels containing beeswax were considered as better formulations in terms of drug permeation and cumulative drug release. All the results were found to be statistically significant (p<0.05, ANOVA) and it was concluded that the beeswax-fish oil combination in oleogel can prove to be beneficial in terms of permeation across the skin and stability.
Keywords: fish oil; penetration enhancer; oleogel; anti-inflammatory